Training on Making 3D Models of Augmented Reality Based Hydrology Education Tools for Teachers - Mukarramah, Siti Khaeratul; Amri, Ariani; Hamdani, Ibnu Mansyur (Pustaka Digital Indonesia, 2023)
Augmented reality in its development in Indonesia has Lots used as an auxiliary medium classroom teaching for learning to become more interactive between teacher and student. Students get Study independent with an observed tool developed augmented reality display without need guided. However sadly Still how difficult development augmented reality application, making Not yet how many teachers can develop application based on augmented reality. on the basis problem such, he did activity devotion to public in form training creation of 3D models based on augmented reality followed by representatives from teachers from all over Palopo as many as 15 teachers. Activity training is shared into 3 sessions, ie session First through method lecture, session second guided tutorial methods and sessions final with practice. Result of implementation training This is a capable teacher making augmented reality application for free independent and capable tool display hydrology based on augmented reality that can be used for enrich classroom learning.